PERTUMBUHAN PENDUDUK DAN PERKEMBANGAN PERMUKIMAN DI KECAMATAN GUNUNG TALANG KABUPATEN SOLOK TAHUN 2009-2019 - Qotrin Nada; Paus Iskarni (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
Population growth is the change in the number of people in a certain area at a certain time compared to the previous time. Increasing population growth also causes areas that are less supportive to be used as places to live, such as unstable, sloping, and unhealthy land. In connection with increasing population growth, the need for residential land for the population will increase. There are 3 factors that influence population growth, namely births, deaths, and migration. This study uses the geometric method to determine the rate of population growth. Analysis of the relationship between population growth factors and settlement development was carried out using the Chi Square test. The results showed that in 2009, birth is the growth factor that most influenced the development of settlements with a Chi Square correlation value of 0.508. Meanwhile, in 2019 in-migration is the factor that most influenced the development of settlements with a Chi Square correlation value of 0.950. This shows that population growth greatly affects the development of settlement area so that it is expected that development planning related to settlement development can be carried out optimally.